Review of Robotic Surgery in Gynecology—The Future Is Here - Lauterbach, Roy (Rambam Maimonides Med J, 2017)
The authors present a systematic review of randomized and observational, retrospective and prospective studies to compare between robotic surgery as opposed to laparoscopic, abdominal, and vaginal surgery for the treatment of both benign and malignant gynecologic indications. The comparison focuses on operative times, surgical outcomes, and surgical complications associated with the various surgical techniques. PubMed was the main search engine utilized in search of study data. The review included studies of various designs that included at least 25 women who had undergone robotic gynecologic surgery. Fifty-five studies (42 comparative and 13 non-comparative) met eligibility criteria. After careful analysis, we found that robotic surgery was consistently connected to shorter post-surgical hospitalization when compared to open surgery, a difference less significant when compared to laparoscopic surgery. Also, it seems that robotic surgery is highly feasible in gynecology. There are quite a few inconsistencies regarding operative times and estimated blood loss between the different approaches, though in the majority of studies estimated blood loss was lower in the robotic surgery group. The high variance in operative times resulted from the difference in surgeon’s experience. The decision whether robotic surgery should become mainstream in gynecological surgery or remain another surgical technique in the gynecological surgeon’s toolbox requires quite a few more randomized controlled clinical trials. In any case, in order to bring robotic surgery down to the front row of surgery, training surgeons is by far the most important goal for the next few years.